FRI0571-PC Primary care guidance for immunology testing in rheumatology: need and impact. (23rd January 2014) - Sharp, C. A.; Rowbottom, A.; Mitchell, W.; Bukhari, M.; Ottewell, L.; Wood, E. F.
Abstract : Background: Guidelines in a tertiary care Rheumatology setting showed a reduction in unnecessary immunology testing, improving efficiency and reducing expenditure (1 ). Objectives: To assess the need for guidance for general practitioners (GPs) requesting immunology tests for patients with a potential Rheumatological diagnosis. To design guidance, implement it and assess its impact. To improve GPs' understanding of these tests and reduce unnecessary testing. Methods: An online survey was emailed to all GPs in the 49 practices in the locality regarding confidence in using immunology tests. Answers ranged from 'Not at all confident' to 'Extremely confident' on a 5-point Likert scale. Respondents stated whether they knew the cost of antibody tests and their need for teaching and online guidance. Consensus guidelines were created following collaboration between Rheumatologists, GP leads, Immunologists, and the Pathology Laboratory, based on original tertiary care guidelines (1 ). These were integrated into the online TQuest requesting system and emailed to GPs. Results: Survey: 44 from ~200 GPs responded, giving a response rate of 23%. 2/3 of respondents felt moderately confident in choosing tests to aid diagnosis of rheumatological disease, with 40% slightly confident. There was greater variation in answers regarding confidence in choosing tests to monitor disease. None knew how much autoantibody tests cost their practice annually. 93% would appreciate teaching in this area, and 96% would appreciate online guidance. Guidance: A local face to face teaching session was arranged. We measured the number of tests requested using TQuest for 3 months prior to guidance introduction (April-June 2012), and 3 months following this (Oct–Dec 2012). Requests for rheumatoid factor (RF) underwent a steady decline, from an average of 438 in the 3 months pre-guidance, to an average of 215 in the final 3 months. Anti-CCP antibody and Complement also declined going from 2.6 to 1.6 requests and 4.3 to 2.6, respectively. Requests for ANA, ENA and dsDNA increased during this period. ANA testing rose from a 3-monthly average of 5.3 to 8.3. ENA rose from 0 to 13 with dsDNA rising from 0 to 5.3. Requests for immunoglobulins and ANCA were static. Because RF was by far the cheapest test, overall the benefits of cost savings from test reductions were equalised by the increase in ANA, ENA and dsDNA. Conclusions: Survey: We demonstrated a range of confidence amongst GPs when requesting immunology tests. A need for teaching and a mandate for the introduction of online guidance was demonstrated. The potential for responder bias existed but such strong results in favour of guidance were encouraging. Guidance: Requests for RF halved, demonstrating that GPs have a better understanding of the utility of the test. Some test requesting frequencies increased. This may be because we raised awareness of the availability of these tests online, or that patients who were not previously having these tests requested appropriately, are now having them requested. We intend to perform a further survey of GPs to assess their satisfaction with the current guidance, and to alter this accordingly. References: Sharp, C.A., Bruce, I.N. (2011). Efficiency in follow-up immunology testing for patients with connective tissue diseases and vasculitis. Clin Med, 11(6), 632-633 Acknowledgements: Mr Tony Crick, Head of Pathology Services. Mr David Slater, IT Lead for Pathology Services Disclosure of Interest: None Declared